Fast Synthesis of Graphene with a Desired Structure via Ni-Catalyzed Transformation of Amorphous Carbon during Rapid Thermal Processing: Insights from Molecular Dynamics and Experimental Study - Li, Xiaowei; Wang, Zhenyu; Li, Hanchao; Wang, Aiying; Lee, Kwang-Ryeol (American Chemical Society, 2019)
Fast transfer-free synthesis of graphene on a given dielectric substrate is achieved by Ni-catalyzed solid-state transformation of amorphous carbon (a-C) through rapid thermal processing (RTP). Nevertheless, the dependence of this transformation behavior on Ni/a-C thickness and the underlying mechanism at the atomic scale are not well comprehended, leading to the lack of efficient synthesis and modulation of the graphene structure experimentally. Here, using reactive molecular dynamics simulation, we select Ni as a catalyst and present a systematic investigation of the diffusion of C into Ni and the corresponding structural transformation of a-C into graphene under different conditions. The results emphasize the decisive role of the Ni/C atomic ratio in the quality and layer number of graphene instead of the Ni or aC thickness. Combined with the results during the cooling process, they suggest that the a-C-to-graphene transformation mechanism is mainly dependent on the diffusion behavior of C and the catalytic effect of Ni, rather than the dissolution/precipitation. Most importantly, both the simulation and experiment propose a universal equation to elucidate the relationship between the number of C and Ni atoms and the RTP graphene structure. This finding not only enables the fast synthesis and modulation of a-C-transformed graphene with the desired structure and layers on various substrates without the transfer process but also gets rid of the limitation of carbon sources and Ni structures and simplifies the RTP process parameters significantly, which can be utilized widely in experiment to promote the commercial application of graphene.